The Influence of the International Labour Organization (ILO) in the Formulation of Migrant Worker Protection Policies in East Java - Adys Cintya Maharani Putri; Gonda Yumitro; M. Subhan Setowara (Utan Kayu Publishing, 2025)
This article examines the influence of the International Labor Organization (ILO) in the drafting of East Java Provincial Regulation No. 2 of 2022 on the Protection of Indonesian Migrant Workers. This topic is important because subnational governments are required to play a role in migrant worker protection, yet the pathways through which global labor norms enter local regulations remain understudied. Using a qualitative approach through interviews and document analysis, the study traces how international principles, particularly the 1990 International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (ICRMW) were incorporated into regional policymaking. The findings show that although no formal collaboration existed between the ILO and the East Java Provincial Parliament, the ILO's influence emerged through the diffusion of global standards on safe migration, fair recruitment, and legal protection, which became substantive references during the drafting process. These results demonstrate that the diffusion of international norms can occur through multi-level governance mechanisms, where international actors shape subnational legislation indirectly through knowledge production and policy advocacy.